PERLINDUNGAN HUKUM TERHADAP KORBAN PENGANIAYAAN DALAM PENANGANAN TINDAK PIDANA DI INDONESIA - Hamid, Hasmiah (Jurnal Ilmiah Ecosystem, 2016)
Legal protection of the rights of victims of persecution that is felt is still minimal when the issue of justice is not only applicable to the abuser alone but also victims of abuse. This happens because of the existence and the legal position of victims of crime in the criminal justice system only as a witness (complainant and victim), where the victim is not part of the elements involved in the criminal justice system as defendants, the police and the prosecutor. Through this research, it is expected that the protection of the rights of victims of persecution in the future be able to immediately take steps, among others in the criminal procedural law, the national provision which is clear, and balanced on the protection of the rights of victims of abuse and for the achievement of law enforcement, it is necessary to do an effort to reform the criminal law or efforts to review and re-establishment (reorientation and reform) the provisions of the criminal procedure law regarding the protection of victims of persecution.